Kosovo, FR Yugoslavia : Medium-Term Public Expenditure Priorities - World Bank (Washington, DC, 2013)
Given the tight overall resource constraints in Kosovo, and in the face of declining donor support and limited access to external finance, difficult choices and trade-offs on spending decisions will need to be made. The main challenge will be to develop expenditure policies which will preserve macro-stability and ensure that public services are sustainable, comprehensive, and efficiently provided. Public spending policies need to lay the basis for broad-based equitable economic growth, and target the most needy, in an effective and efficient fashion. Through introducing the Medium Term Expenditure Framework (MTEF) approach in 2002, the United Nations Interim Administration in Kosovo (UNMIK) and the Provisional Institutions of Self Government (PISG) have started to make progress in adding a medium-term context to budget policy. This report identifies the several important expediture measures that require action. First, spending has to be reallocated across sectors, so reduce subsidies, reassess public sector employment, and provide finance for investment needs. Second, improve the efficiency of existing spending in the health, education, and social protection sectors. Third, increase the budget spending on health to provide a greater range of services and target educational finance to reduce inequality. Fourth, strengthen the effectiveness of the budget as a policy tool. Fifth, further improve transparency and accountability.